Застосування нейромережевого підходу в задачах прогнозування забруднення пластинчастих теплообмінників - Пирогов, В. О. (ХНУРЕ, 2023)
The problem of the dynamics of contamination of plate heat exchangers is relevant, as it affects the efficiency and cost-effectiveness of the operation of heat exchangers. Contamination of heat exchanger plates can lead to reduced heat exchange, increased energy consumption and equipment wear. The application of artificial intelligence and machine learning can help solve this problem.